2018
DOI: 10.1542/hpeds.2017-0120
|View full text |Cite
|
Sign up to set email alerts
|

Use of Intranasal Dexmedetomidine as a Solo Sedative for MRI of Infants

Abstract: IN dexmedetomidine is an effective solo sedative agent for MRI in infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 23 publications
2
27
0
1
Order By: Relevance
“…Intranasal dexmedetomidine offers an alternative approach for pediatric sedation . In previous studies, the overall success rate of intranasal dexmedetomidine for pediatric procedural sedation ranged from 87% to 96.2%, which is consistent with our findings . However, the potential hemodynamic effects of intranasal dexmedetomidine sedation (hypotension and bradycardia) are a key concern.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Intranasal dexmedetomidine offers an alternative approach for pediatric sedation . In previous studies, the overall success rate of intranasal dexmedetomidine for pediatric procedural sedation ranged from 87% to 96.2%, which is consistent with our findings . However, the potential hemodynamic effects of intranasal dexmedetomidine sedation (hypotension and bradycardia) are a key concern.…”
Section: Discussionsupporting
confidence: 91%
“…17 In previous studies, the overall success rate of intranasal dexmedetomidine for pediatric procedural sedation ranged from 87% to 96.2%, which is consistent with our findings. 18,19 However, the potential hemodynamic effects of intranasal dexmedetomidine sedation (hypotension and bradycardia) are a key concern. There is no clear consensus on the definition of bradycardia in the pediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a starting dose of 3 μg/kg was used in many of our patients who had failed to complete MRI scans with IN dexmedetomidine as a sole agent. This was lower than what was used in prior studies, which had shown that a higher dose of 4 μg/kg was associated with better outcomes and lower rate of anaesthetic rescue (4,26). This suggests that long and rest-disruptive procedures-in particular MRI scans-should be performed with a higher dose of sedation.…”
Section: Discussionmentioning
confidence: 69%
“…One study of the application of dexmedetomidine Intranasal by Olgun et al stated a dose of 4 µg/kg was proven effective in providing a sedative effect in infants aged 1 to 12 months. 5 This study determined the dose based on several previous studies. In a study by Sulton et al, the use of dexmedetomidine IN 3 mg/kg was proven to be effective in children's MRI procedures, without side effects.…”
Section: Dexmedetomidine Dosagementioning
confidence: 99%